PENDIDIKAN MULTIKULTUR DI INDONESIA - Sumaryati, Sri (PKn Progresif, 2008)
It can not be denied that the historical record clearly Indonesia is a country consisting of multi-ethnic, cultural, and religious. When applied to the management of this state with a uniform system of course will cause counter-productive problems. Therefore, to build a pluralistic country, each of these differences should be accommodated, particularly through multicultural education.